The Asian Green Revolution - Hazell, Peter B. R. (International Food Policy Research Institute, 2009)
The Green Revolution brought modern science to bear on a widening Asian food crisis in the 1960s. The speed and scale with which it solved the food problem was remarkable and unprecedented, and it contributed to a substantial reduction in poverty and the launching of broader economic growth in many Asian countries. Improved cereal varieties, fertilizers, irrigation, and modern pest control methods lay at the heart of the Green Revolution, yet it was much more than a technology fix. It also required a supporting economic and policy environment. The need for markets that could handle the surge in production and the need to educate farmers about the new technology and ensure that they had access to the inputs and receive an adequate reward to their investments, led governments across Asia to actively intervene in launching and implementing the Green Revolution. Government interventions were also important for ensuring that small farmers were included in the revolution and did not get left behind. Even with the success of the Green Revolution, there are remaining social and environmental problems that still need to be resolved and a continuing need to increase yields to meet Asia’s growing food needs. There is also urgent need to bring the Green Revolution in an appropriately modified form to Sub-Saharan Africa.